(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we generalize modus tollens method for neutrosophic digraph by using neutrosophic rule and define degree of a vertex in neutrosophic digraph, Indegree of a vertex in neutrosophic digraph, out degree of a vertex in neutrosophic digraph and generalized modus tollens are discussed.